TEACHERS' PERCEPTIONS OF THE IMPORTANCE OF INTRODUCING ENGLISH AT AN EARLY AGE - Risky Mayasari, Adhe (Jurnal Ecoment Global, 2024)
This research emphasizes the importance of teaching English in early childhood to support cognitive and social development. English as an international language is essential in global communication, so its mastery is an urgent need for modern society, including Indonesia. Mastery of English is necessary for a child to look at life in the future. This research wants to know a teacher's perception towards his students to learn English as early as possible. With a qualitative approach and data collection from documentation accompanied by questionnaires, the results show that, according to the teachers, challenges such as lack of teacher training and low motivation in students can be overcome with school support and interactive teaching methods. In addition, the early introduction of English improves children's language skills and prepares them for further education and an increasingly connected world. Therefore, schools and educators need to improve competencies through continuous training, providing adequate resources, and developing exciting and relevant teaching strategies.